(untitled) (Revista Española de Fisiología, 1993)
Plasma levels of ethanol and acetate, which is the end product of hepatic ethanol oxidation, have been studied in 60 rats. Animals were divided into two groups: 1) Control rats, and 2) Alcohol-treated rats. Ethanol and acetate were measured without any previous handling (endogenous levels) and after intraperitoneal injection of a single dose of ethanol. Blood specimens were taken at 30, 60, 120, 180 and 240 minutes after ethanol injection. Plasma levels of ethanol and acetate were performed by Head Space Gas Chromatography. Alcohol-treated animals had higher plasma acetate levels than control ones. There were statistically significant differences for acetate between both groups of rats at 0, 30, 120 and 180 minutes.